Analysis of Cooling Energy Efficiency in Optimizing the Façade Design of the Emergency Unit of RSUD Ar Rozy Kota Probolinggo - Ghina Nabiel Sukma; Dian Ariestadi (G-Tech: Jurnal Teknologi Terapan, 2025)
Electricity consumption in Indonesia has been rising at an average rate of approximately 5% per year, with commercial buildings particularly hospitals accounting for about 23% of this demand. As a continuously operating healthcare facility, RSUD Ar Rozy Kota Probolinggo exhibits substantial cooling energy requirements. Previous studies have shown that approximately 63.9% of hospital energy consumption is attributed to cooling systems, while building façades contribute between 20–50% of total energy use and 50–60% of overall heat gain. This study aims to evaluate the existing façade design of the emergency unit at RSUD Ar Rozy Kota Probolinggo, to identify strategies that can effectively reduce cooling energy consumption. A quantitative approach was employed using computational simulations through the EDGE Buildings software. The analysis involved assessing the energy efficiency of various design modifications, including adjustments to the WWR, the addition of sun shading elements, and the implementation of energy-efficient glazing materials. The results revealed that a façade configuration consisting of a 25.28% WWR, an overhang with an AASF of 0.42, and Stopray Vision 38T glass achieved a reduction in cooling energy consumption of 44.28%, equivalent to 20,680 kWh per month compared to the existing design. This configuration successfully met the EDGE Buildings energy efficiency criteria, achieving total energy savings of 28.74%. Therefore, the proposed façade design is recommended as an optimal retrofit solution to enhance energy efficiency and promote sustainable hospital building design.